2015
DOI: 10.1016/j.diii.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Overview of digital breast tomosynthesis: Clinical cases, benefits and disadvantages

Abstract: In France, the national breast cancer-screening program is based on mammography combined with clinical breast examination, and sometimes breast ultrasound for patients with high breast density. Digital breast tomosynthesis is a currently assessed 3D imaging technique in which angular projections of the stationary compressed breast are acquired automatically. When combined with mammography, clinicians can review both conventional (2D) as well as three-dimensional (3D) data. The purpose of this article is to rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 45 publications
(78 reference statements)
0
11
0
1
Order By: Relevance
“…Numerous previous reports have confirmed that using DBT causes the increase of the detection efficiency of malignant lesions in the mammary glands, and the decrease in the number of false negative results and the reduction of repeated calls of patients for supplementary tests with false positive results [6][7][8][9]. Digital breast tomosynthesis is more sensitive than fullfield digital mammography in detecting focal lesions in the breast.…”
Section: Architectural Distortion (Ad)mentioning
confidence: 87%
See 2 more Smart Citations
“…Numerous previous reports have confirmed that using DBT causes the increase of the detection efficiency of malignant lesions in the mammary glands, and the decrease in the number of false negative results and the reduction of repeated calls of patients for supplementary tests with false positive results [6][7][8][9]. Digital breast tomosynthesis is more sensitive than fullfield digital mammography in detecting focal lesions in the breast.…”
Section: Architectural Distortion (Ad)mentioning
confidence: 87%
“…Main advantages of DBT technique in comparison with FFDM are high-contrast visibility, greater visibility of the margins of pathological masses and more precise determination of lesion size [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BT remains under investigation as a complementary screening tool to MG. More masses and architectural distortion lesions are detected with tomosynthesis (1113,1517). Our aim was to evaluate non-calcified lesions detected only on BT.…”
Section: Discussionmentioning
confidence: 99%
“…Using the combo-mode, within the same examination, 2D digital mammography and tomosynthesis are performed, with the advantage for the radiologist to compare the information provided by the two modalities and to increase the accuracy of the interpretation, but also with the disadvantage for the patient due to the risk of the increased irradiation dose. The replacement of 2D mammography with the synthesized 2D images from tomosynthesis might reduce with almost 50% the irradiation dose, and this is the subject of many studies conducted in the present [ 1 , 11 , 12 ].…”
Section: Technical Basics Of Tomo-synthesismentioning
confidence: 99%